The diagnostic challenges of differentiating metastatic extramammary Paget disease and prostatic adenocarcinoma: A case report and review of the literature - Gregory Palmateer; Edouard H. Nicaise; Jatin Gandhi; Taylor Goodstein; Michelle Sheng; Kenneth Ogan; Omer Kucuk; Melinda Yushak; Martin G. Sanda; Keith A. Delman; Viraj Master (Urology Case Reports)
Extramammary Paget disease (EMPD) is a rare dermatologic malignancy with a high rate of recurrence and increased risk for developing secondary malignancies. We present a 74-year-old male with previously resected primary EMPD who presented with widespread PSMA-avid lesions without prostatic uptake, an elevated PSA >100, and a negative prostate biopsy. Based on this and immunohistological staining, recurrent EMPD was suspected. However, after additional staining and reexamining their clinical presentation, metastatic prostate cancer without a detected primary lesion is more probable. This case highlights the diagnostic challenge variable expression of shared biomarkers found in EMPD and prostate cancer present to clinicians.